Calcium hydride with aluminium for thermochemical energy storage applications - Desage, Lucie; Humphries, Terry; Paskevicius, Mark; Buckley, Craig (2023)
Thermochemical energy storage has the potential to unlock large-scale storage of renewable energy sources by integrating with power production facilities. Metal hydrides have high thermochemical energy storage densities through reversible hydrogenation. Particularly, calcium hydride presents remarkable properties to integrate with high-temperature systems. The addition of aluminium to calcium hydride enables lower operating temperatures below 700 °C. The CaH2-2Al system reacts through a two-step reaction mechanism, which was verified via in situ powder diffraction analysis. The thermodynamics of dehydrogenation have been determined for both dehydrogenation steps with step 1 having a ΔHdes = 79 ± 3 kJ mol−1 and ΔSdes = 113 ± 4 J mol−1 K−1, while step 2 has a ΔHdes = 99 ± 4 kJ mol−1 and ΔSdes = 128 ± 5 J mol−1 K−1. The reaction kinetics for both steps were determined using the Kissinger method from DSC-TGA data to be 138 ± 12 kJ mol−1 and 98 ± 8 kJ mol−1 for step 1 and 2, respectively. Reversible hydrogenation over step 2, for 66 cycles at 670 °C under 20 bar of H2, determined the sorption capacity to be stable at 91% of the theoretical maximum of 1.1 wt% H2. A materials-based cost analysis evaluates the system at 9.2 US$ per kW hth, with an energy density of 1031 kJ kg−1